TRAFFIC PERFORMANCE EVALUATION AND ANALYSIS OF Al-FALLAH INTERSECTION IN BAGHDAD CITY UTILIZING SYNCHRO.10 SOFTWARE - Tarish Ziboon, Abdul-Razzak; Ibrahim Qasim, Zaynab; Ali Yousif, Maysam (Journal of engineering and sustainable development (Online), 2019)
Transportation is an essential element for the development of countries economically, socially, and culturally. The progress in countries is measured through the progress in transportation systems and urban road networks. Al-Fallah intersection which lies northeastern of Baghdad city considered one of the highly congested urban centers, suffers congestion, particularly during morning and evening peak hours. The objective of this study is to analyze the delay time, degree of saturation, level of service in Al-Fallah intersection in Baghdad city using Synchro.10 software, in addition, to evaluate and analyze the intersection for choosing the best suggestion. The technique of video recording has been used for collecting the traffic volume data for all approaches from 7a.m to 4 p.m. for three days: Monday, Tuesday, and Wednesday. The operation analysis of isolated signalized intersection provides valuable and important information about the performance of the transportation systems in the city.The through movements of Al-Fallah Street illustrate the movement from the center of Al-Sadir city to Al-Rusafa and in reverse, they represent the heaviest traffic volumes in the Al-Fallah intersection. The Results of the analysis specified that the Al-Fallah intersection works under a level of service F with an average control delay of (322.1) seconds per vehicle and degree of saturation (2.56) v/c during the peak hours